2018
DOI: 10.1002/admi.201800353
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Cost Fabrication of Large‐Area Broccoli‐Like Multiscale Micro‐ and Nanostructures for Metallic Super‐Hydrophobic Surfaces with Ultralow Water Adhesion and Superior Anti‐Frost Ability

Abstract: Metallic super‐hydrophobic surfaces with ultralow water adhesion are essential for a wide variety of applications, such as enhanced condensation heat transfer and anti‐icing applications. Broccoli‐like multiscale micro‐ and nanostructures composed of four different microscale and nanoscale features are fabricated on different metal surfaces by an inexpensive nanosecond laser system in this study. The surface shows high stability during evaporation, and the surface water adhesion of this structure is only 1.4 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Inspired by natural lotus leaves [ 2 ], rose petals [ 3 ], and butterfly wings [ 4 ], super-hydrophobic surfaces (i.e., apparent contact angle above 150° and sliding angle below 10°) have been successfully mimicked through the synergetic effects of micro/nanostructure fabrication and surface chemical modification [ 5 , 6 , 7 , 8 , 9 , 10 ]. Due to their enormous potential applications including anti-icing [ 11 ], drag reduction [ 12 ], self-cleaning [ 13 ], anti-bacteria [ 14 ], and corrosion resistance [ 15 ], super-hydrophobic surface mimicry has been extensively developed by state-of-the-art techniques, such as thermal imprinting [ 16 , 17 ], chemical vapor deposition [ 18 ], coating [ 19 ], electrochemical deposition [ 20 , 21 ], and laser texturing [ 22 , 23 , 24 , 25 , 26 , 27 ]. Particularly, laser texturing can be seen as one of the facile approaches, and therefore can be extensively utilized to fabricate super-hydrophobic substrates owing to its precise control of surface fabrication with three dimensional (3D) hierarchical structures [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by natural lotus leaves [ 2 ], rose petals [ 3 ], and butterfly wings [ 4 ], super-hydrophobic surfaces (i.e., apparent contact angle above 150° and sliding angle below 10°) have been successfully mimicked through the synergetic effects of micro/nanostructure fabrication and surface chemical modification [ 5 , 6 , 7 , 8 , 9 , 10 ]. Due to their enormous potential applications including anti-icing [ 11 ], drag reduction [ 12 ], self-cleaning [ 13 ], anti-bacteria [ 14 ], and corrosion resistance [ 15 ], super-hydrophobic surface mimicry has been extensively developed by state-of-the-art techniques, such as thermal imprinting [ 16 , 17 ], chemical vapor deposition [ 18 ], coating [ 19 ], electrochemical deposition [ 20 , 21 ], and laser texturing [ 22 , 23 , 24 , 25 , 26 , 27 ]. Particularly, laser texturing can be seen as one of the facile approaches, and therefore can be extensively utilized to fabricate super-hydrophobic substrates owing to its precise control of surface fabrication with three dimensional (3D) hierarchical structures [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by hierarchical surface structures developed by nature [1,2], intensive research efforts employing different methods including chemical etching [3], two-step etching process [4], chemical vapor deposition [5], incorporation of inhibiting agents [6] and laser texturing [7,8] have been invested in the production of similar functionalized surfaces in the laboratory environment in the last decade. Several studies have shown that the surface morphology and chemistry on micro- and nanoscale can be efficiently controlled also by femtosecond [7,8,9,10], picosecond [11] and nanosecond [12,13,14,15,16] laser pulses as well as by continuous wave (CW) lasers [17]. Such laser-induced micro-/nanostructuring leads to a significant improvement of the surface functionality and opens up completely new possibilities in the field of surface engineering [18] for a wide range of applications in photonics, tribology, wettability, heat transfer, and biomedicine [19,20,21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, this (super)hydrophilic state is not stable. Consequently, such a textured surface exposed to the air at ambient conditions can develop hydrophobicity with contact angle exceeding 150° and roll-off angle (RoA) below 5° [13,16,25,34]. Under suitable conditions, the final, hydrophobic state becomes stable.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is important to seek for new ways to make/replicate such special structures as simply as possible in a well-controlled manner, as well as to further exploit the corresponding potentials in diverse applications. Among these applications, from the perspective of surface engineering, a self-similar morphological surface with a high fractal dimension often has a relative larger surface area and hence demonstrates higher performance in multiple fields such as super hydrophilicity or hydrophobicity for anti-fog or self-cleaning, low friction, high (catalysis) reactivity, controlled anisotropic behaviors, and highly efficient radical particle entangling [ 28 , 29 , 30 , 31 , 32 , 33 ]. However, the investigation of such self-similar surface fabrication and application development has not been thoroughly conducted according to the existing literature.…”
Section: Introductionmentioning
confidence: 99%